The most sought-after minority group? The first months of four newly-graduated male teachers - Ottesen, Andri Rafn; Jóhannesson, Ingólfur Ásgeir (Netla, 2019)
The possible shortage of teachers at compulsory school level in Iceland, and the decreasing proportion of male teachers at the same school level has been discussed in recent years. These discussions, especially on the status of male teachers, have sparked our interest in performing this study. This is also an international debate concerning the notion that male teachers might become “extinct” at primary level (e.g., McGrath and Van Bergen, 2017).The background of the study constitutes two often separate bodies of research. On the one hand research on novices in teaching and, on the other, studies focusing on male teachers. The article reports a study where we interviewed four newly-graduated male teachers three times during their first six months: First in August 2017 before teaching commenced, then in late October or November the same year, and, lastly, at the end of January or in early February 2018. They taught in four schools in different parts of the country. We asked them how they felt they were doing in their practice and whether they had experienced anything that could be related to their gender. Our main research question was twofold: How do newly-graduated male teachers adjust to their new field of practice, and do they need specific support measures because of their gender?In the article, we report three prominent themes in the interview data: Firstly, the experience of the new field of practice and the working environment. The interviewees emphasized that they had not encountered any serious obstacles and were pleased with the work, although they did at times have long working hours under some amount of stress. They said it had been rather easy to get to know the students; however, parent cooperation was the area they were most insecure about, especially in the beginning.The second theme is the novice male teachers’ experience of the mentoring and supervision they received. None of them had a specially assigned mentor, apart from school administration members, but all had been told that they could ...